Input-Output Analysis of Deindustrialization and Outsourcing - Erika Stracová; Richard Kališ (University of Economics in Bratislava, Department of Economic Policy, 2017)
The paper deals with the topic of deindustrialization as a process of a decreasing relative importance of manufacturing. While the decrease of manufacturing in major developed and developed economies is undeniable, the developing and newly industrialized economies are starting to experience this phenomenon as well. The results of the paper show that the so-called premature deindustrialization is mainly caused by outsourcing. Furthermore, the data suggest the existence of an upper limit of outsourcing for major developed economies. In these economies, the decrease of manufacturing is more likely caused by other relevant factors. Last but not least, a few transition economies face to a slightly decreasing value of outsourcing on a much lower level. This could be explained by a fragmentation of the entire value chain across the European Union. The empirical results are based on the Input-Output methodology, the observation period of fifteen years from 2000 to 2014 and a sample of 43 countries.
Keywords: C67; L60; 330; input-output analysis; deindustrialization; outsourcing